2013
DOI: 10.3109/01612840.2013.789943
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Postpartum Traumatic Stress in Mothers with Preterm Infants: Manual Development and Evaluation

Abstract: Premature birth has been associated with multiple adverse maternal psychological outcomes that include depression, anxiety, and trauma as well as adverse effects on maternal coping ability and parenting style. Infants and children who are premature are more likely to have poorer cognitive and developmental functioning and, thus, may be harder to parent. In response to these findings, there have been a number of educational and behavioral interventions developed that target maternal psychological functioning, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 55 publications
(86 citation statements)
references
References 40 publications
2
81
1
2
Order By: Relevance
“…The entire intervention is manualized; it can be easily taught to individuals without specialized training in psychological treatments; and treatment fidelity, as measured by the therapists' adherence to the written manual, was high both across sessions and across therapists. 28 Data from other settings have suggested a relationship between disturbances of attachment and traumatic stress reactions in mothers with a history of interpersonal violence. Schechter and Willheim 51 found that greater severity of maternal PTSD was associated with lower maternal baseline salivary cortisol levels and greater likelihood of distorted, inflexible, and negative mental representations of the child.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…The entire intervention is manualized; it can be easily taught to individuals without specialized training in psychological treatments; and treatment fidelity, as measured by the therapists' adherence to the written manual, was high both across sessions and across therapists. 28 Data from other settings have suggested a relationship between disturbances of attachment and traumatic stress reactions in mothers with a history of interpersonal violence. Schechter and Willheim 51 found that greater severity of maternal PTSD was associated with lower maternal baseline salivary cortisol levels and greater likelihood of distorted, inflexible, and negative mental representations of the child.…”
Section: Figurementioning
confidence: 99%
“…Treatment fidelity to all components of the intervention, as measured by the therapists' adherence to the written manual, was high both across sessions and across therapists. 28 The intraclass correlation between raters varied between 0.78 and 0.80 (P , .001), which is considered a high level of reliability. 31 …”
Section: Training and Supervisionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 An additional 3 sessions were developed for a subset of the intervention group, with content directed at identifying triggers associated with the development of parental trauma symptoms as well as education about parenting patterns associated with the aspects of the vulnerable child syndrome. 29 Participants in the information/usual-care comparison group received one 45-minute information session on the policy, procedures, and environment of the NICU, with education about parenting the premature infant.…”
Section: Interventionmentioning
confidence: 99%
“…The intervention, which incorporated components of trauma-focused cognitive behavior therapy (CBT), was found to be feasible and easily delivered in the NICU environment and received high ratings of maternal satisfaction. 19 However, whether these symptomatic benefits continue after the infants return home is unknown. In this report, we describe the 6-month follow-up outcome data of our study participants and hypothesize that mothers in the intervention group will continue to show statistically significant reductions in symptoms of trauma, anxiety, and depression compared with mothers in the comparison group.…”
mentioning
confidence: 99%